Revitalisasi Pendidikan Karakter Pancasila sebagai Solusi Krisis Moral Siswa di Era Society 5.0 - R. Anis Yuliawati Putri; Jatim Desiyanto; Amirul Mukminin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
This study aims to describe the implementation of character education within Civics (PPKn) instruction, the character values ​​fostered, and the obstacles encountered during its application in the fifth-grade class at SDN Panggung 2 Sampang. Employing a descriptive qualitative method, the study focused on the Grade V/A teacher and fifth-grade students as subjects. Conducted in 2025, the research utilized data collection techniques such as observation, interviews, and documentation, with data validity verified through triangulation. The results indicate that the implementation of character education encompasses planning, execution, and evaluation. Lesson planning integrated character education, although the plans were not created independently by the teacher. Implementation involved specific instructional activities and methods, spontaneous actions, the instilling of discipline, and the creation of a conducive learning atmosphere. The teacher fostered three key character values—in accordance with Ministry of National Education guidelines—through various learning activities. Obstacles identified included limited facilities and infrastructure, a lack of variety in teaching methods, low student enthusiasm, and limited communication between the teacher and parents. These findings highlight the importance of facility support, methodological innovation, and parental involvement in enhancing the effectiveness of character education within Civics instruction.